2005
DOI: 10.3168/jds.s0022-0302(05)72727-2
|View full text |Cite
|
Sign up to set email alerts
|

Dry Matter Intake is Decreased More by Abomasal Infusion of Unsaturated Free Fatty Acids than by Unsaturated Triglycerides

Abstract: Previous experiments from our group have demonstrated that abomasal infusion of unsaturated free fatty acids (FFA) markedly decreases dry matter intake (DMI) in dairy cows. In contrast, experiments from other groups have noted smaller decreases in DMI when unsaturated triglycerides (TG) were infused postruminally. Our hypothesis was that unsaturated FFA would be more potent inhibitors of DMI than an equivalent amount of unsaturated TG. Four Holstein cows in late lactation were used in a single reversal design.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
72
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(92 citation statements)
references
References 26 publications
13
72
5
Order By: Relevance
“…Moreover, increased amounts of unsaturated FA infused to the abomasum (Bremmer et al, 1998) or fed to dairy cows (Harvatine and Allen, 2005;Moallem et al, 2007) have been shown to decrease the feed intake. Litherland et al (2005) showed a negative correlation between DMI and plasma concentrations of glucagon-like peptide 1 amide (7 to 36; GLP-1) in cows abomasally infused with long-chain FA as free fatty acids or triglycerides forms, which was not observed for cholecystokininoctapeptide (CCK-8). However, in a recent study reported by Relling and Reynolds (2007), higher concentrations in plasma of GLP-1 and CCK-8 were shown in cows fed monounsaturated FA or PUFA as compared with cows fed saturated FA.…”
Section: Resultsmentioning
confidence: 92%
“…Moreover, increased amounts of unsaturated FA infused to the abomasum (Bremmer et al, 1998) or fed to dairy cows (Harvatine and Allen, 2005;Moallem et al, 2007) have been shown to decrease the feed intake. Litherland et al (2005) showed a negative correlation between DMI and plasma concentrations of glucagon-like peptide 1 amide (7 to 36; GLP-1) in cows abomasally infused with long-chain FA as free fatty acids or triglycerides forms, which was not observed for cholecystokininoctapeptide (CCK-8). However, in a recent study reported by Relling and Reynolds (2007), higher concentrations in plasma of GLP-1 and CCK-8 were shown in cows fed monounsaturated FA or PUFA as compared with cows fed saturated FA.…”
Section: Resultsmentioning
confidence: 92%
“…Supplements of plant oils and oilseeds typically decrease DMI when included in amounts above 50 g of oil/kg of DM, a response often attributed to the adverse effect of unsaturated FA on rumen microbial communities, lowered ruminal OM and NDF digestion (Allen, 2000;Lock and Shingfield, 2004), and an increase in gut peptide secretion (Litherland et al, 2005;Relling and Reynolds, 2007). By design, incremental inclusion of CO in concentrate supplements increased the FA content of the total diet from 33 to 60 g/kg of DM.…”
Section: Dmimentioning
confidence: 99%
“…Compared Figure 4 Relationship between the amount of 18:2n-6 (K) or 18:3n-3 (J) infused at the abomasum and mammary secretion of 18:2n-6 and 18:3n-3 in lactating cows. Data derived from experiments involving infusions of examining the effects of post-ruminal infusion of soya oil (Litherland et al, 2005), soya fatty acids (Litherland et al, 2005;Ortiz-Gonzalez et al, 2007) and linseed oil (Petit et al, 2002;Kazama et al, 2010). Solid line indicates the relationship:-18:2n-6 milk 5 0.488 3 18:2n-6 infused 1 17.67 (n 5 11, R 2 5 0.968, P , 0.001) and the dotted line indicates the relationship:-18:3n-3 milk 5 0.499 3 18:3n-3 infused 1 3.55 (n 5 11, R 2 5 0.942, P , 0.001).…”
Section: Altering the Fatty Acid Composition Of Ruminant Meatmentioning
confidence: 99%